PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SDN CENTRE MANGALLI KECAMATAN PALANGGA KABUPATEN GOWA - Tri Apri Sari Nurhayati; Nasaruddin; Bhakti Prima Findiga Hermuttaqien (STKIP Subang, 2023)
This study aims to describe the application of the think pair and share cooperative learning model in improving social studies learning outcomes for fifth grade students at SDN Center Mangalli. The approach used is a qualitative approach. This type of research is classroom action research (PTK) which is carried out in two cycles and each cycle is held in two meetings. Each cycle goes through 4 stages, namely the planning stage, the implementation stage, the observation stage, and the reflection stage. The focus of this research is the focus of the process and focus of learning and documentation. The subjects of this study were 25 class V teachers and fifth grade students consisting of 17 male students and 8 female students. In this study, the researcher acted as the executor of the action and the class teacher as the observer. Data analysis techniques are qualitative and quantitative. The results showed that the application of the cooperative learning model type think pair and share in cycle I was 56% (enough) of students who passed with an average student score of 67.6. Then in cycle II there was an increase to 92% (very good) of students who passed with an average student score of 86.4. Based on the analysis of social studies learning outcomes, it can be concluded that there is an increase in social studies learning outcomes of students by using the think pair and share cooperative learning model.